Kajian Tekno Ekonomi Potensi Sampah Kota Pontianak Sebagai Sumber Pembangkit Listrik Tenaga Uap (PLTU) - Budiman, Aris (Faculty of Engineering, Universitas Tanjungpura, 2016)
Abstract– One of the city problem is waste and one of the reasons is the community lifestyle and denser population due to the high growth rate. Therefore, the problem of waste needs immediate and significant solutions. One of the solutions is to build the Steam Power Plant fueled by organic waste in Pontianak City. In this thesis will be analyzed theinitial aspects of Steam Power Plant construction fueled by organic waste both technically and economically. This study proposes the feasibility assessment of construction. The research regarding the waste potency especially organic waste in Pontianak City as a source of Steam Power Plant is able to produce 2.87 MW of electrical output power. Furthermore, the economic cost of the Steam Power Plant construction is Rp. 119,833,472,771,- with a Payback Period of 2.69 years which the economic lifetime of the Steam Power Plant up to 25 years, Net Present Value (NPV) of Rp. 279,032,579522.70,- , Internal Rate of Return (IRR) of 30.37 % , and Benefit Cost Ratio (BCR) of 2.98. Keywords– techno-economic, waste, Steam Power Plant, electrical